Is there a way to show this other than with calculus and implicit differentiation? I am able to easily do this, but I was wondering if there was another way to show it. I feel I may be missing something obvious or going down unnecessary rabbit trails because I have tried using the Diophantus chord method.

Using the chord method, I have that the equation of the tangent line would have the form $Y=t(X-3)+5$ where t is some rational slope.

I then substituted this into $0=X^3-Y^2-2$.
Eventually, I get to $0=(X-3)(X^2+(3-t^2)X+(9+3t^2))$.

The first factor gives the known solution of $X=3$ and I tried to use the quadratic formula to solve the second factor but then only led me a nasty looking expression with a square root, which leads me to believe I am wrong since I am looking only for rational solutions. I also feel that I have gone down the wrong path because even if I do have success with the chord method, I would only have parameterized the rational solutions to $y^2=x^3-2$ and not actually found the equation of the tangent line.

If someone could guide me toward a method of finding the tangent to $y^2=x^3-2$ at (3,5) without the use of calculus (or point out what I am missing) that would be awesome. Thank you!


Y^2 = x^3 + 2

2y. dy/dx = 3x^2

The gradient of the tangent to the curve at (3,5) is

  1. dy/dx|(x=3 ,y=5) = 27

m= 27/10

since (3,5) lies on the curve y - 5 = 27/10(x-3)

y= (-81+50)/10 + 27x/10

y = 27x/10 - 31/10 is the required equation of the tangent the that curve at the rational point (3,5)

  • $\begingroup$ Sketch the graph of the function, if you don't want calculus $\endgroup$ – Abdulhafeez Abdulsalam Feb 17 '18 at 22:32
  • $\begingroup$ I don't understand why this has been upvoted. OP explicitly asked for a solution that doesn't use calculus. $\endgroup$ – pjs36 Feb 17 '18 at 23:20

Another method, borrowed from algebraic geometry:

Change origin, setting $x=3+h$, $y=5+k$. The equation of the tangent is the linear part of the equation in $h,k$. Thus \begin{align}y^2=x^3-2&\iff (5+k)^2=(3+h)^3-2\iff 25+10k+k^2=27+27h+9h^2+h^3-2\\ &\iff h^3+9h^2-k^2+27h-10k=0. \end{align} So the equation of the tangent w.r.t. the new origin is $$27h-10k=0\iff27(x-3)-10(y-5)=0\iff 27x-10y=31.$$

  • $\begingroup$ Thanks for the answer, that is a slick way to do it! I have one question, how do we know that the linear part of the h,k equation is going to be the equation of the tangent at x=0? $\endgroup$ – Aaron Hultstrand Feb 18 '18 at 15:36
  • $\begingroup$ This is a polynomial function (in two variables), and so it is equal to its Taylor expansion. In a Taylor expansion, the linear part corresponds to the tangent. $\endgroup$ – Bernard Feb 18 '18 at 16:09

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.